Inclusion of Health in Environmental Impact Assessment of Major Transport Infrastructure Projects in Vietnam - Tracy Pham; Emily Riley; Patrick Harris (Kerman University of Medical Sciences, 2018)
Background Infrastructure spending, especially in the transport sector, is expected to increase rapidly in Vietnam. This boost in transportation investment impacts health. Environmental impact assessments (EIAs) are essential tools for decision-making to reduce and mitigate anticipated impacts of development projects, and integration of health assessment as an essential part of the EIA process has been regulated in many high-income countries. There is, however, limited knowledge about how health is evaluated in these environmental assessments in low- and middle-income countries (LMICs) such as Vietnam. Methods We did an analysis of EIAs of four major transport projects in Vietnam, applying a six-step coding framework previously used to investigate EIAs in the Australian context. Results We found that health was inadequately considered in all four EIAs. There was no direct health assessment within the four EIAs due to the lack of formal requirements from either Government or the financing agency, the Asian Development Bank (ADB). Health issues were often identified as risks posed by the projects within the assessment of impacts on environmental conditions. A broader consideration of health was limited. When social outcomes of the projects were present in EIAs, they were often mentioned once without any detailed assessment or linking to health. There was no evidence linking health benefits and shifts towards active travel with the construction of two metro rail projects. Mitigation measures offered in all four EIAs were found to be generic and insubstantial. Conclusion The health assessments in the EIAs of four transport projects in Vietnam were significantly less detailed than those in Australia, mainly due to the lack of legislative requirements. The lack of health content indicates the need for involvement of health experts in the environmental assessment process, as well as requirements for the health assessment to be integrated in EIA. Our findings suggest there is the need to build capacity both within and outside of government to fully consider the health impacts of infrastructure in EIA practice.